A New Genus, Ectemnoides, for Seven Species of Australian Gondwanan Simuliidae (Diptera) With Description of a Novel Form of Larval Attachment. Issue 4 (10th August 2018) - Moulton, John K; Currie, Douglas C; Craig, Douglas A
Abstract: A segregate of Australian simuliids of Gondwanan provenance with unusual attributes is assigned to a new genus— Ectemnoides . Only one species was originally known, that from females of the eastern Australian (Victoria) Paracnephia umbratorum (Tonnoir) and its presumed larvae, which we fully confirm here. Three previously unknown related species, Ectemnoides acanthocranius n. sp., Ect. faecofilus n. sp. and Ect. uvulatus n. sp. from Western Australia are described. These four species have numbers of unusual synapomorphies. Of note is the habit of larvae of Ect. umbratorum and Ect. faecofilus to attach to the ends of constructed threads apparently composed of larval fecal pellets and other material, enclosed within a salivary silk matrix. The four species all have short spine-like setae on the larval head capsule and their body physiognomy is unusual, with head large in relation to a tubular body, with that being semitransparent when alive. Three other Western Australia simuliids, Ect. absitus n. sp., Ect. princeae n. sp. and Ect. sp. A., possess more typical attributes. Known larvae of the first two of these simuliids lack the marked head setae; however, in common with Ect. acanthocranius of the previous segregate, larvae of the three taxa lack the anal sclerite and have markedly low numbers of hooks comprising the posterior circlet. Details are given for distribution and, where known, bionomics. Trichomycetes are recorded for the second time from simuliids in Western Australia, from Ect. sp. A. Brief character analysis is provided, as are comments regarding historical biogeography.